Experimental Study of Pressure Pulsation in a Mixed-Flow Pump with Different Tip Clearances Based on Wavelet Analysis - Leilei Ji; Wei Li; Weidong Shi; Ling Zhou; Ramesh Agarwal (Shock and Vibration)
In order to investigate the effect of various impeller tip clearances on the pressure pulsation in a mixed-flow pump, the energy performance test and pressure pulsation experiment of a mixed-flow pump with different tip clearances are studied simultaneously. The pressure pulsation signals at impeller inlet, middle, and oulet are processed and analyzed by the wavelet transform. The results show that the change of tip clearance can affect the head and efficiency of mixed-flow pump. Under designed flow rate, when the tip clearance increases from 0.2 mm to 1.1 mm, the head and efficiency decrease by 18.1% and 11.6%, respectively. Due to the strong influence of blade passing frequency (BPF) at impeller middle, the period of pressure pulsation curve is about 1/4 of impeller rotation period. At impeller inlet, the low-frequency pulsation with energy concentration is the main disturbance frequency, and, with the increase of tip clearance, not only does the high-value region of wavelet spectrum expand to low-frequency direction but also it is easy to form second-order peaks in the time-averaged wavelet curve. At impeller outlet, affected by BPF and rotor-stator interaction (RSI), the high-frequency disturbance in RSI area decreases first and then increases. The wavelet coherence demonstrates the stable low-frequency disturbances in comparison to others and it will affect the flow field at impeller middle.